Extent and causes of increased domestic violence during the COVID-19 pandemic: community health worker perspectives from Kenya, Bangladesh, and Haiti - Ann Gottert; Tim Abuya; Sharif Hossain; Alain Casseus; Charlotte Warren; Pooja Sripad (Journal of Global Health Reports)
# Background Emerging data, media reports, and anecdotal evidence suggest that domestic violence (DV) has increased during the COVID-19 pandemic. However, more detailed data are needed on the magnitude, forms, and causes of DV during COVID-19 in different contexts worldwide. We sought to contribute such evidence from the perspective of community health workers (CHWs) in low-middle income countries in three different regions of the world.